25-Hydroxyvitamin D, Insulin Resistance and Cardiovascular Risk in Young Latino Children Who Are Overweight/Obese (P21-060-19). (13th June 2019) - Bustillos, Gennesy; Gallo, Sina; Jones, Margaret; Mehlenbeck, Robyn
Abstract: Objectives: The aim of the study is to examine the relationship between 25-hydroxyvitamin D (25(OH)D) concentrations, insulin resistance and lipid profiles among Latino children who are overweight/obese. Methods: Data from 59 children (65% male, 90% obese, mean ± SD age: 7.6 ± 1.5, range: 4–10 years) participating in a pediatric weight management program were analyzed at baseline. Adiposity (BMI-for-age percentile), % body fat, homeostatic model assessment-insulin resistance (HOMA-IR) and fasting lipids were examined in relation to serum 25(OH)D concentrations using Spearman correlation statistics. Vitamin D status was categorized as deficiency (25(OH)D ≤20 ng/mL), insufficiency (20–30 ng/mL) and sufficiency (≥30 ng/mL). Insulin resistance and lipids were compared among vitamin D groups using a Kruskal-Wallis H test. Results: Mean 25(OH)D concentration for the entire cohort was 19.4 ± 7.4 ng/ml with 33% categorized as vitamin D deficient and 52% as insufficient. Serum 25(OH)D was statistically inversely associated with BMI (Spearman's ρ = −0.276, P  = 0.043) and HOMA-IR (Spearman's ρ = −0.601, P  < 0.001) although, there were no significant correlations with all other variables. There was a statistically significant difference in HOMA-IR between the vitamin D categories ( P  < 0.001) with a mean rank score of 39.3 for children who were vitamin D deficient, 22.6 for insufficient and 18.0 for sufficient. Conclusions: In this sample of Latino children who were predominately obese, vitamin D deficiency and insufficiency were high. Circulating 25(OH)D concentrations were associated with insulin resistance although, not with other cardiovascular disease risks. Funding Sources: Potomac Health Foundation.